Mengolah Potensi Jagung Lokal: Pelatihan Nugget Jagung untuk Ketahanan Pangan Masyarakat Desa - Titin Nurhidayati; Muhammad Febriyansah Satriyo Priyan; Luvena Azzahra Farid; Putri Ulan Dani; Putri Maula Sari; Putri Fransiska Dina Maretha; Nur Kholifah; Dwi Agus Prabowo; Sidqi Aqdam Himaya; Nabila Uzzah Qithrotun Nada; Rina Ismawati; Mahrus Ali; Ahmad Setya Budi (Ngarsa: Journal of Dedication Based on Local Wisdom, 2025)
Food security is a strategic issue in sustainable rural development. Cakru Village, Kencong District, Jember Regency, has abundant corn production, yet its utilization is largely limited to fresh consumption and animal feed, resulting in low value added and limited food diversification. This community service program aimed to enhance residents’ skills in processing corn into corn nuggets, a nutritious, marketable local food innovation. Using the Asset-Based Community Development (ABCD) approach, the program involved stages of discovery, dream, design, and destiny. The results demonstrated an improvement in participants’ knowledge and skills in processing corn into nuggets, as indicated by increased pre-test and post-test scores and the ability to independently carry out the production process in accordance with procedural and hygienic standards. Participants also applied simple marketing strategies, including product packaging, pricing, and marketing simulations. In addition, the establishment of a corn-based joint business group supported program sustainability and showed potential to strengthen food security and increase the value added of local corn. Keywords: Food Security; Corn; Corn Nuggets; Local Food Innovation Abstrak: Ketahanan pangan merupakan isu strategis dalam pembangunan berkelanjungan di wilayah pedesaan. Desa Cakru, Kecamatan Kencong, Kabupaten Jember, memiliki potensi produksi jagung yang melimpah, namun pemanfaatannya masih terbatas pada konsumsi segar dan pakan ternak, sehingga nilai tambah dan diversifikasi pangan lokal belum optimal. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan keterampilan warga dalam mengolah jagung menjadi nugget jagung sebagai inovasi pangan lokal yang bergizi dan bernilai jual. Program ini menggunakan pendekatan Asset-Based Community Development (ABCD) yang meliputi tahapan discovery, dream, design, dan destiny. Hasil kegiatan menunjukkan peningkatan pengetahuan dan keterampilan peserta dalam pengolahan jagung menjadi nugget, yang ditunjukkan oleh kenaikan skor pre-test dan post-test serta kemampuan mempraktikkan proses produksi secara mandiri sesuai prosedur dan prinsip higienitas. Peserta juga mampu menerapkan strategi pemasaran sederhana melalui penentuan kemasan, harga jual, dan simulasi pemasaran. Selain itu, terbentuk kelompok usaha bersama berbasis olahan jagung sebagai upaya keberlanjutan program, yang berpotensi memperkuat ketahanan pangan dan meningkatkan nilai tambah jagung lokal. Kata kunci: Ketahanan Pangan, Jagung, Nugget Jagung, Inovasi Pangan Lokal